Design and performance analysis of a stick making machine to support the sustainability of palm oil leaf waste - Wahyudi; Indra Setiawan; Eduardus Dimas Arya Sadewa; Fattiya Hamada Sakti Isa Putri; Muhammad Rifa'i; Ibnu Ferianto; Nurani Adristi Bunga Nirvana; Gusti Ivan Indie Mahardika (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
The palm oil industry is a key sector in Indonesia, yet it produces significant amounts of leaf waste, which has been underutilized and has the potential to pollute the environment. The fundamental problem currently lies in the largely manual process of utilizing leaf waste, making it inefficient for large-scale production. This research aims to design a machine for making palm leaf stick-making from palm leaf waste to support sustainability principles. The method used is Reverse Engineering to analyze and improve the existing machine design, with a focus on the function, capacity, and safety aspects. This data collection was done through field surveys and Focus Group Discussions (FGD). The expected result of this research is a more efficient palm leaf and frond separating machine design, with a target performance of 1.5 kg per 10 minutes (9 kg/hour). The design's advantage lies in the ease of maintenance, especially in removing and replacing shaft and chopping blade components. This research can answer the needs of industry and society for environmentally friendly appropriate technology, thus supporting sustainable waste management. The palm oil industry is a cornerstone of Indonesia's economy, yet it generates substantial amounts of leaf waste that remain largely underutilized, presenting a significant environmental management challenge. The fundamental problem lies in the reliance on manual processing methods, which are inefficient and unsuitable for large-scale waste valorization. This study aimed to design and analyze a stick machine to process palm oil leaf waste, thereby supporting sustainability principles and circular economy initiatives. The research methodology applied was Reverse Engineering, which was used to systematically evaluate and improve upon an existing machine design, with specific attention to enhancing function, operational capacity, and safety. Data collection was conducted through comprehensive field surveys and Focus Group Discussions (FGD) with stakeholders to ensure the design met practical needs. The resulting prototype, powered by a 3 HP electric motor, demonstrated a calculated processing capacity of 9 kg per hour (equivalent to 1.5 kg per 10 minutes). Structural analysis confirmed the machine's robustness, with a calculated shaft safety factor of 3.48, ensuring reliability under operational loads. The design prioritizes ease of maintenance, featuring a mechanism that simplifies the removal and replacement of the shaft and chopping blade components. Furthermore, the machine's operation is environmentally friendly, contributing to waste reduction. In conclusion, this research successfully developed a feasible, efficient, and sustainable technical solution for managing palm oil leaf waste, offering a valuable appropriate technology for both industry and local communities.